Culture-Independent Analyses Reveal Novel Anaerolineaceae as Abundant Primary Fermenters in Anaerobic Digesters Treating Waste Activated Sludge - McIlroy, Simon J.; Kirkegaard, Rasmus H.; Dueholm, Morten S.; Fernando, Eustace; Karst, Søren M.; Albertsen, Mads; Nielsen, Per H. (Frontiers in Microbiology, 2017)
Anaerobic digestion for biogas production is reliant on the tightly coupled synergistic activities of complex microbial consortia. Members of the uncultured A6 phylotype, within the phylum Chloroflexi, are among the most abundant genus-level-taxa of mesophilic anaerobic digester systems treating surplus sludge from wastewater treatment plants, yet are known only by their 16S rRNA gene sequence. This study applied metagenomics to obtain a complete circular genome (2.57 Mbp) from a representative of the A6 taxon. Preliminary annotation of the genome indicates these organisms to be anaerobic chemoorganoheterotrophs with a fermentative metabolism. Given their observed abundance, they are likely important primary fermenters in digester systems. Application of fluorescence in situ hybridisation probes designed in this study revealed their morphology to be short filaments present within the flocs. The A6 were sometimes co-located with the filamentous Archaea Methanosaeta spp. suggesting potential undetermined synergistic relationships. Based on its genome sequence and morphology we propose the species name Brevefilum fermentans gen. nov. sp. nov.